From Frankfurt to Budapest: the paradoxes of a Marxist psychology (Psicologia USP, 1991)
The individual's theory is between parentheses, from a marxist point of view. Ultimate goal to be reached by the social praxis, the individual is not yet, rigorously speaking, while arc remaining the impeding conditions to the development of this moulding historical potentiality. For this reason, the Th. Adorno's Social Psychology may be considered as a Negative Psychology because it denounces the human subjectivity reification under the impact of the social capitalist relations. In Agnes Heller's philosophical work, the individual is viewed as an ideal type whose empirical support is found in the new tendencies and needs that arc rising up from the man of capitalist modernity. Anyway, the scientifical statute of Psychology is under discussion as its ultimate goal the individual - is not yet historically objectivized.